Genocide and resistance Nr. 27(1) - Zizas, Rimantas; Rukšėnas, Alfredas; Buchaveckas, Stanislovas; Bubnys, Arūnas; Makauskas, Bronius; Burinskaitė, Kristina (Genocidas ir rezistencija, 2010)
Full Issue